Analisis Teori Sosiologi Hukum Pada Peristiwa Eksploitasi Pengamen dan Anak Jalanan Dibawah Umur - Nurdin, Aulia Anjani; Anjani, Axara Alejendra; Rasmitha, Nadia Risa; Alvaro, Radiyya; Manurung, Abraham; Yuli, Yuliana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Child welfare is an order of life for children that can guarantee normal growth, both spiritually, physically and socially. The aim of this research is to find out and describe the exploitation of minors. With primary and secondary data types, the data collection technique uses data reduction, presenting the data after the collected data is analyzed and a conclusion is drawn. The results of this research show that the factors causing exploitation of minors are: 1) Low family economy. Their parents' income, which is an average of only 300,000 to 500,000 per month, cannot meet the family's needs, coupled with the relatively large number of family dependents, this creates a heavy burden for low-income families to fulfill their needs. 2) The influence of the child's environment and community, the environment where the child lives and the surroundings the child socializes with, including the child's friends, can be the reason the child takes to the streets. 3) People's low education has an impact on children's education, where parents should have an important role in providing motivation and support for children regarding the importance of education. 4) Cracks and violence in parents' domestic lives, the relationship between parents (father and mother) can influence children take to the streets as there are frequent quarrels between father and mother, separation caused by father or mother leaving home and remarrying or even divorce between father and mother. The suggestion in this research is that parents should be able to carry out their obligations as parents towards their children, such as providing love and not taking away their children's rights, including employing them as newspaper sellers and buskers.